N2 Fixation in Trichodesmium Does Not Require Spatial Segregation from Photosynthesis - Weicheng Luo; Keisuke Inomura; Han Zhang; Ya-Wei Luo (mSystems, 2022)
ABSTRACT The dominant marine filamentous N2 fixer, Trichodesmium, conducts photosynthesis and N2 fixation during the daytime. Because N2 fixation is sensitive to O2, some previous studies suggested that spatial segregation of N2 fixation and photosynthesis is essential in Trichodesmium. However, this hypothesis conflicts with some observations where all the cells contain both photosystems and the N2-fixing enzyme nitrogenase. Here, we construct a systematic model simulating Trichodesmium metabolism, showing that the hypothetical spatial segregation is probably useless in increasing the Trichodesmium growth and N2 fixation, unless substances can efficiently transfer among cells with low loss to the environment. The model suggests that Trichodesmium accumulates fixed carbon in the morning and uses that in respiratory protection to reduce intracellular O2 during the mid-daytime, when photosynthesis is downregulated, allowing the occurrence of N2 fixation. A cell membrane barrier against O2 and alternative non-O2 evolving electron transfer also contribute to maintaining low intracellular O2. Our study provides a mechanism enabling N2 fixation despite the presence of photosynthesis across Trichodesmium. IMPORTANCE The filamentous Trichodesmium is a globally prominent marine nitrogen fixer. A long-standing paradox is that the nitrogen-fixing enzyme nitrogenase is sensitive to oxygen, but Trichodesmium conducts both nitrogen fixation and oxygen-evolving photosynthesis during the daytime. Previous studies using immunoassays reported that nitrogenase was limited in some specialized Trichodesmium cells (termed diazocytes), suggesting the necessity of spatial segregation of nitrogen fixation and photosynthesis. However, attempts using other methods failed to find diazocytes in Trichodesmium, causing controversy on the existence of the spatial segregation. Here, our physiological model shows that Trichodesmium can maintain low intracellular O2 in mid-daytime and achieve feasible nitrogen fixation and growth rates even without the spatial segregation, while the hypothetical spatial segregation might not be useful if substantial loss of substances to the environment occurs when they transfer among the Trichodesmium cells. Our study then suggests a possible mechanism by which Trichodesmium can survive without the spatial segregation.